Nanocellulose-silver ensembles for ultrasensitive SERS: An investigation on the role of nanocellulose fibers in the generation of high-density hotspots. (September 2020) - Nabeela, Kallayi; Thomas, Reny Thankam; Mohamed, A.P.; Pillai, Saju
Highlights: TEMPO-oxidized nanocellulose fibers as a labyrinth for the synthesis of silver nanoconstructs comprising anisotropic and/or spherical structures as efficient SERS platforms with longer shelf-life (>2 years). Ultra-trace detection of two analytes (4-methylbenzenethiol and methyl parathion) up to femtomolar (10 −15 M) level sensitivity. SERS intensity mapping studies of 4-methylbenzenethiol at femtomolar concentration revealed a local enrichment mechanism of analyte driven by nanocellulose-silver ensemble. Nanocellulose-silver colloid upon drying resulted in the formation of high-density hotspot responsible for single molecule SERS (SMSERS) sensitivity. Abstract: Large scale hotspot engineering is a significant approach for the development of highly efficient surface enhanced Raman scattering (SERS) platforms. Herein, 2, 2, 6, 6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized nanocellulose fiber (T-NCF) serves as a labyrinth for developing highly sensitive and stable silver-based SERS platform enabling single molecular level SERS detection of analytes. The SERS activity of 4-methylbenzenethiol (4-MBT) in silver nanoconstructs with dissimilar size and shape (denoted as Ag/NCF-I and Ag/NCF-II systems) synthesized by varying T-NCF to Ag + ratio, exhibited femtomolar sensitivity regardless of their structural variation. A detailed investigation of the SERS performance of both systems with 4-MBT at extremely low concentration (10 −15 M) is carried out with the help of large-area Raman intensity mapping in order to evaluate the role of T-NCF in Raman signal enhancement. The analytical enhancement factors (AEFs) for Ag/NCF-I and Ag/NCF-II are calculated to be 1.4 × 10 12 and 4.8 × 10 11, respectively. A mechanism of local enrichment of analytes is postulated anticipating the ability of flexible nanocellulose fibers to congregate AgNPs, resulting in induced plasmonic coupling of local electromagnetic fields and high-intensity hotspot generation. The potential of T-NCF in generating hotspots can be considered as an alternative strategy to develop standards with long-term colloidal stability and scale-up production of highly sensitive AgNP based plasmonic platforms. This investigation ascertains the potential of nanocellulose fibers in the development of a robust lithography-free SERS sensing platform with single molecule level sensitivity. Graphical abstract: Image, graphical abstract